The RNA modification N 6 -methyladenosine as a novel regulator of the immune system - Shulman, Ziv; Stern-Ginossar, Noam (Nature immunology, 2020)
Protection from harmful pathogens depends on activation of the immune system, which relies on tight regulation of gene expression. Recently, the RNA modification N -methyladenosine (m A) has been found to play an essential role in such regulation. Here, we summarize newly discovered functions of m A in controlling various aspects of immunity, including immune recognition, activation of innate and adaptive immune responses, and cell fate decisions. We then discuss some of the current challenges in the field and describe future directions for uncovering the immunological functions of m A and its mechanisms of action.